2022
DOI: 10.3389/fmicb.2022.824192
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Grazing Exclusion Alters Soil Bacterial Co-occurrence Patterns Rather Than Community Diversity or Composition in Temperate Grasslands

Abstract: Grazing exclusion is one of the most common practices for degraded grassland restoration worldwide. Soil microorganisms are critical components in soil and play important roles in maintaining grassland ecosystem functions. However, the changes of soil bacterial community characteristics during grazing exclusion for different types of grassland remain unclear. In this study, the soil bacterial community diversity and composition as well as the co-occurrence patterns were investigated and compared between grazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…This suggests that grazing reduces the stability of soil bacterial communities compared to grasslands without grazing treatment (Mougi & Kondoh, 2012). Our findings indicate that grazing exclusion promotes higher bacterial network complexity, which differs from studies in temperate grasslands and could be a result of the harsh climate of the Tibetan Plateau, where microorganisms require complex linkages to optimize limited resources (Marcos et al, 2019; Wang, Li, et al, 2022).…”
Section: Discussioncontrasting
confidence: 69%
“…This suggests that grazing reduces the stability of soil bacterial communities compared to grasslands without grazing treatment (Mougi & Kondoh, 2012). Our findings indicate that grazing exclusion promotes higher bacterial network complexity, which differs from studies in temperate grasslands and could be a result of the harsh climate of the Tibetan Plateau, where microorganisms require complex linkages to optimize limited resources (Marcos et al, 2019; Wang, Li, et al, 2022).…”
Section: Discussioncontrasting
confidence: 69%
“…Previous studies have reported that grazing may affect soil microbial diversity ( Zhang et al, 2016 ; Wang et al, 2022a ; Jing et al, 2023 ), however, findings have been mixed. Wu et al (2022) conducted a regional-scale grazing experiment on the Mongolian Plateau (covered three typical vegetation types) and showed that grazing increased the diversity of both bacterial and fungal compared with enclosure.…”
Section: Introductionmentioning
confidence: 96%
“…Soil microorganisms ( e.g. , bacteria and fungi) are the vital component of biodiversity and play important roles in the grassland ecosystem, such as litter decomposition, soil nutrient supply, the elements’ biogeochemical cycle, which regulate the plant nutrient availability ( Bardgett, 2005 ; Yao, Bowman & Shi, 2011 ; Zhang et al, 2016 ; Zhao et al, 2020 ; Wang et al, 2022a ). The loss of microbial diversity leads to the decline in ecosystem functions, which negatively impacts on primary production, nutrient cycling and climate regulation ( Delgado-Baquerizo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, native grass hay is the traditional method of native grass; however, because the quality and palatability of natural hay is sensitive to environmental factors, it is not feasible to address the seasonal and annual imbalances through hay preparation techniques ( Li et al., 2015 ). Ensiling, a traditional method of preserving animal feed and fresh fodder crops, provides feed for animals all year round, effectively reducing nutritional losses and extending storage time ( Wang et al., 2022 ). Silage was mainly lactic acid bacteria (LAB) in the anaerobic environment using soluble carbohydrates for fermentation, produce lactic acid (LA), leading to low pH, inhibit aerobic bacteria, effective preservation of nutrients and improves feed palatability ( Cai et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%